Comprehensive study on accounting procedures of recordkeeping for USA retirement savings plan (401k) of USA in Data-Path Ltd. - Priyo Hossain, Shaikh Pran (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.